COVID-19 격리병동 입퇴원 환자의 외상후 스트레스 장애 증상 및 관련 요인 - 김민정; 김지혜; 곽세현; 이은혜; 박진영; 이덕종 (Singyŏng chŏngsin ŭihak, 2024)
Objectives Pandemic diseases like COVID-19 could affect people even after they are cured. In this study, we asked COVID-19 survivors whether they showed post-traumatic stress disorder (PTSD) symptoms, and tried to figure out what factors can affect their symptoms. Methods Approximately 3 months after their discharge, a psychological survey was conducted with 83 adults (38 men and 45 women, mean age 38.6±11.3 years) who had been hospitalized with COVID-19 in an isolation ward. The group was divided according to the presence or absence of PTSD symptoms, and differences in demographic, psychological, and hospitalizationrelated factors between the groups were analyzed using the independent t-test. We conducted hierarchical multiple regression analysis exploring variables affecting PTSD symptoms. Results Fourteen of the survey respondents (15.8%) reported experiencing PTSD symptoms, including partial PTSD symptoms. The group with PTSD symptoms appeared to have more pain upon admission to hospital, compared to the group without PTSD symptoms. The group with PTSD symptoms showed higher anxiety and depression than the group without PTSD symptoms, and their physical quality of life was found to be low. The presence of PTSD symptoms seemed to be influenced by anxiety sensitivity. Conclusion Our findings suggest that hospitalization in an isolation ward due to COVID-19 may be associated with the development of PTSD symptoms. Anxiety sensitivity could influence the level of PTSD symptoms after discharge. The results of this study suggest the need to monitor and care for the mental health of patients admitted to and discharged from isolation wards due to infection. KCI Citation Count: 0